Caged - Simmons-Smith, Talia (Te Kaharoa, 2021)
There I stood, in the middle of a moment that uttered assumptions of me, of my people. It was so subtle but hardly dismissible. It turned my insides and left a heavy weight in my chest. I felt like I couldn’t speak, like a puppet controlled by my environment, ruled by what others had been brainwashed to believe, what I had believed, dominated and bound to this cage.